2015
DOI: 10.3390/inorganics3040482
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Covalency in Cerium and Uranium Hexachlorides: A Correlated Wavefunction and Density Functional Theory Study

Abstract: The electronic structure of a series of uranium and cerium hexachlorides in a variety of oxidation states was evaluated at both the correlated wavefunction and density functional (DFT) levels of theory. Following recent experimental observations of covalency in tetravalent cerium hexachlorides, bonding character was studied using topological and integrated analysis based on the quantum theory of atoms in molecules (QTAIM). This analysis revealed that M-Cl covalency was strongly dependent on oxidation state, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 54 publications
9
58
0
Order By: Relevance
“…Few systematic density-based studies investigating the dependency of covalent bond character on metal oxidation state exist. Beekmeyer and Kerridge analysed DFT-, RASSCF and-CASSCFderived [UCl 6 ] nÀ (n = 0-3) densities 65 and determined that, while only weak covalency, as evidenced by r BCP and d(U,Cl) measures, was present, oxidation state dependence was pronounced, see Table 3. The authors found that, irrelevant of the simulation method used, covalent bond character was most pronounced in the highest (+6) oxidation state, with r BCP values for the lowest (+3) some 60% lower.…”
Section: Oxidation State Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Few systematic density-based studies investigating the dependency of covalent bond character on metal oxidation state exist. Beekmeyer and Kerridge analysed DFT-, RASSCF and-CASSCFderived [UCl 6 ] nÀ (n = 0-3) densities 65 and determined that, while only weak covalency, as evidenced by r BCP and d(U,Cl) measures, was present, oxidation state dependence was pronounced, see Table 3. The authors found that, irrelevant of the simulation method used, covalent bond character was most pronounced in the highest (+6) oxidation state, with r BCP values for the lowest (+3) some 60% lower.…”
Section: Oxidation State Dependencymentioning
confidence: 99%
“…Beekmeyer and Kerridge have performed the same analysis to identify (n + 1)d and nf bonding contributions in [MCl 6 ] nÀ , where M = Ce and U. 65 Comparing DFT to RASSCF/CASSCF generated densities, they found that the former gave delocalisation indices consistently higher than the latter. However, the majority of this increase could be attributed to the ungerade (i.e.…”
Section: D-and F-shell Contributions To Covalencymentioning
confidence: 99%
“…The Ce-O distances in five-coordinate 6(py) [2.101(1) -2.120(1) Å] are similar to those observed in seven-coordinate complex 3 or six-coordinate [Ce(OSiPh 3 ) 4 (DME)] [Ce-O Si 2.098(1) -2.133(1) Å], [5] but slightly shorter than found in the metallasilsesquioxane complex [Ce-{(c-C 6 H 11 ) 8 [25] Considering the different bonding in tetra-and trivalent cerium complexes, [55] an increasing contribution of π-backbonding between the non-bonding oxygen orbitals and to some degree stronger involved 5d and 4f-orbitals in Ce IV relative to Ce III complexes is expected. [32d, [55][56][57][58][59] Accordingly, 6(py) displays longer Si-O Ce bond lengths (ΔSi-O Ce : 0.030-0.034 Å) in comparison with 7, which is the result of weakened bonds due to an increase in π-backbonding within the Ce-O bond. As a consequence, also less bent Ce-O-Si bond angles are measured in the structure of the Ce IV complex.…”
Section: [Cecl 6 ] (Cac Me ) Toward Naosir 3 (R = Et Ipr)mentioning
confidence: 99%
“…This is due partly to the experimental difficulties associated with obtaining high quality experimental electron densities on radioactive systems featuring very heavy elements, and partly a function of the QTAIM only recently being extended to quantum chemical studies of the actinide elements. Indeed, we were the first group to extensively employ the QTAIM in this capacity, and have used it to study both covalency [6][7][8][9][10][11][12][13][14][15][16][17][18] and bond strength [19][20][21] in a range of molecular f element systems.…”
Section: Introductionmentioning
confidence: 99%